Doctor role modelling in medical education: BEME Guide No. 27. (4th July 2013) - Passi, Vimmi; Johnson, Samantha; Peile, Ed; Wright, Scott; Hafferty, Fred; Johnson, Neil
Abstract : Aim: The aim of this review is to summarise the evidence currently available on role modelling by doctors in medical education. Methods: A systematic search of electronic databases was conducted (PubMed, Psyc- Info, Embase, Education Research Complete, Web of Knowledge, ERIC and British Education Index) from January 1990 to February 2012. Data extraction was completed by two independent reviewers and included a quality assessment of each paper. A thematic analysis was conducted on all the included papers. Results: Thirty-nine studies fulfilled the inclusion criteria for the review. Six main themes emerged from the content of high and medium quality papers: 1) the attributes of positive doctor role models; 2) the personality profiles of positive role models; 3) the influence of positive role models on students' career choice; 4) the process of positive role modelling; 5) the influence of negative role modelling; 6) the influence of culture, diversity and gender in the choice of role model. Conclusions: This systematic review highlights role modelling as an important process for the professional development of learners. Excellence in role modelling involves demonstration of high standards of clinical competence, excellence in clinical teaching skills and humanistic personal qualities. Positive role models not only help to shape the professional development of our future physicians, they also influence their career choices. This review has highlighted two main challenges in doctor role modelling: the first challenge lies in our lack of understanding of the complex phenomenon of role modelling. Second, the literature draws attention to negative role modelling and this negative influence requires deeper exploration to identify ways to mitigate adverse effects. This BEME review offers a preliminary guide to future discovery and progress in the area of doctor role modelling.